2013
DOI: 10.1186/2192-0567-3-20
|View full text |Cite
|
Sign up to set email alerts
|

Floating layer formation, foaming, and microbial community structure change in full-scale biogas plant due to disruption of mixing and substrate overloading

Abstract: Background: The use of biogas as renewable resource of energy is of growing interest. To increase the efficiency and sustainability of anaerobic biogas reactors, process failures such as overacidification, foaming, and floating layers need to be investigated to develop sufficient countermeasures and early warning systems to prevent failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
(41 reference statements)
1
20
0
Order By: Relevance
“…Recently, two research papers have been published dealing with foam formation in manure digesters due to organic overloading [12,13]. To our knowledge, there exist only two papers dedicated to foam formation in a full-scale biogas plant treating biogenic waste until now [5,14]. Lienen et al [5] analyzed the formation of floating layer and foam in a full-scale biogas plant treating biogenic waste.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, two research papers have been published dealing with foam formation in manure digesters due to organic overloading [12,13]. To our knowledge, there exist only two papers dedicated to foam formation in a full-scale biogas plant treating biogenic waste until now [5,14]. Lienen et al [5] analyzed the formation of floating layer and foam in a full-scale biogas plant treating biogenic waste.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there exist only two papers dedicated to foam formation in a full-scale biogas plant treating biogenic waste until now [5,14]. Lienen et al [5] analyzed the formation of floating layer and foam in a full-scale biogas plant treating biogenic waste. The authors demonstrated that both phenomena can be reduced by proper stirring and well-controlled substrate feeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VFA/TIC ratio is generally used for routine checking of biogas plants [3] as this method is cheap and simple. This parameter also showed a good predictive ability for process upsets in the case of the over-acidified AD plant described in this paper, as is also shown in Table 3.…”
Section: Process Upset Indicatorsmentioning
confidence: 99%
“…However, there are issues still remaining unclear. The most common upsets of the biogas process are over-acidification [1] as well as the formation of foam [2] and floating layers [3].…”
Section: Introductionmentioning
confidence: 99%